A LITERATURE RESEARCH OF THE RELATIONSHIP BETWEEN LEADERSHIP, ORGANIZATIONAL AGILITY, ORGANIZATIONAL PERFORMANCE AND ORGANIZATIONAL STRUCTURE IN MANAGING UNCERTAINTY IN THE VUCA WORLD (Third Sector Social Economic Review, 2025)
The VUCA world is becoming increasingly complex and challenging for both individuals and organizations. Knowledge, experiences, practices, and strategies acquired in the past do not always provide solutions for today's world. The speed of change necessitates the acceleration of organizational processes. The increasing uncertainties compel organizations to continuously reassess their strategies, agility, leadership roles, and responses to change. Most studies have focused on implementing tools, techniques, processes, and methodologies to enhance the success of uncertainty management and have provided recommendations in this regard (Grote, 2004; Koh et al., 2005; Karlsen, 2011; Johansen et al., 2014; Minciu et al., 2020; Lima et al., 2021; Matsunaga, 2021). The primary aim of this study is to conduct a literature review on the relationships between leadership, organizational agility, organizational performance, and organizational structure in the context of managing uncertainties in today's VUCA world. Based on the findings, the study aims to propose a conceptual model.
Keywords: VUCA; Leadership; Organizational Agility; Organizational Performance; Organizational Structure